(3TQM Sde GdYdhe ddHgGQjs - (3Gdehdhj GdgfOj, eMeO eHjf, J (B1225 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf GdXGgQ Cf GSe HeYfi GdJSHjM hefUhH jaYd eVeQ hgh SHMJ hGdJSHjM GdJfRjg hgh GdJHQg Yf GdShAs
(3BNQgG (B:s
(3bGd GdeUfa adG jUM GdJYQja Hg EdG JYQja daXjG hPdc HYOe GdEaGOI EdG hLhO GdGNJUGQ abW GdMce efg ELeGdj hgh GdcTGa GdGJMGO Hjf GdCeQjf hab hGMOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 18s
(3eYLe GdeDdajf (B3 / 615s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs